Perfil sociodemográfico da AIDS no Espírito Santo no período de 2006 a 2015 (Revista Brasileira de Pesquisa em Saúde/Brazilian Journal of Health Research, 2019)
Sociodemographic profile of AIDS patients in Espírito Santo state, Brazil, from 2006 to 2015